Uses and Gratifications of Digital Signage and Relationships with User Interface. Issue 5 (19th October 2016) - Bae, Young Han; Jun, Jong Woo; Hough, Michelle
ABSTRACT: This study explores motivational factors related to digital signage (DS) uses and gratification and evaluates the viability of a suggested research model incorporating user interface. We found convenient information, entertainment, and benefits to be motivational factors of DS uses and gratification. These factors influenced the perceived affordance and active control of user interface. Among user interface constructs, affordance affected active control, which in turn influenced user experiences of DS. In addition, this study found that the factor of benefits also directly influenced user experiences. These results reveal important insights to DS researchers as well as to out-of-home advertisers and marketers.